Kepribadian Tokoh Ana Dalam Novel Pelangi Dan Hujan Antara Kenangan Dan Angan Angan Karya Orina Fazrina - Septy Widya Larasati; Rangga Surya Fajri; Eva Dwi Kurniawan (Jurnal Pendidikan, Bahasa dan Budaya, 2024)
This study employs a qualitative approach with a descriptive method, where the data analyzed consists of words and quotations taken from the novel "Rainbows and Rain" by Orina Fazrina. The primary data source for this research is the novel itself, identified as "Rainbows and Rain" by Orina Fazrina. Data collection methods involve reading and note-taking, utilizing suitable research instruments. Data analysis encompasses the stages of data reduction, data presentation, and drawing conclusions. . The results of this study will be mangulas using Sigmun Freud's Theory of Personality (Id, Ego and Superego). In addition, this study will also analyze the character of the main character Ana in the novel Rainbow and Rain Between Memories and Wishful Thinking by Orina Fazrina.